Anticancer redox activity of gallium nanoparticles accompanied with low dose of gamma radiation in female mice - Eman I Kandil; Sawsan M El-sonbaty; Fatma SM Moawed; Ola MS Khedr (Tumor Biology)
Guided treatments with nanoparticles and radiotherapy are a new approach in cancer therapy. This study evaluated the beneficial antitumor effects of γ-radiation together with gallium nanoparticles against solid Ehrlich carcinoma in female mice. Gallium nanoparticles were biologically synthesized using Lactobacillus helveticus cells. Transmission electron microscopy showed gallium nanoparticles with size range of 8−20 nm. In vitro study of gallium nanoparticles on MCF-7 revealed IC 50 of 8.0 μg. Gallium nanoparticles (0.1 mg/kg body weight) were injected intraperitoneally daily on the seventh day of Ehrlich carcinoma cells inoculation. Whole-body γ-radiation was carried out at a single dose of 0.25 Gy on eighth day after tumor inoculation. Biochemical analysis showed that solid Ehrlich carcinoma induced a significant increase in alanine aminotransferase activity and creatinine level in serum, calcium, and iron concentrations in liver tissue compared to normal control. Treatment of Ehrlich carcinoma–bearing mice with gallium nanoparticles and/or low dose of γ-radiation exposure significantly reduced tumor volume, decreased alanine aminotransferase and creatinine levels in serum, increased lipid peroxidation, and decreased glutathione content as well as calcium and iron concentrations in liver and tumor tissues with intense DNA fragmentation accompanied compared to untreated tumor cells. Moreover, mitochondria in the treated groups displayed a significant increase in Na+/K+-ATPase, complexes II and III with significant reduction in CYP450 gene expression, which may indicate a synergistic effect of gallium nanoparticles and/or low dose of γ-radiation combination against Ehrlich carcinoma injury, and this results were well appreciated with the histopathological findings in the tumor tissue. We conclude that combined treatment of gallium nanoparticles and low dose of gamma-radiation resulted in suppressive induction of cytotoxic effects on cancer cells.